2000
DOI: 10.1038/sj.ejhg.5200479
|View full text |Cite
|
Sign up to set email alerts
|

An essential SMN interacting protein (SIP1) is not involved in the phenotypic variability of spinal muscular atrophy (SMA)

Abstract: The survival motor neuron (SMN) protein and the SMN interacting protein 1 (SIP1) are part of a 300 kD protein complex with a crucial role in snRNP biogenesis and pre-mRNA splicing. Both proteins are colocalised in nuclear structures called gems and in the cytoplasm. Approximately 96% of patients with autosomal recessive spinal muscular atrophy (SMA) show mutations in the SMN1 gene, while about 4% fail to show any mutation, despite a typical SMA phenotype. Additionally, sibs with identical 5q13 homologs and hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
(41 reference statements)
1
7
1
Order By: Relevance
“…Although patients within families exhibited identical alterations in the SMN gene, they showed variations in disease phenotype indicative of other disease modifying genes. Thus, it was concluded that Gemin2 mutations are rare and they do not function as a disease modifier in SMA (29). However, this study did not address the point whether levels of Gemin2 protein are altered in these patients by mechanisms such as, for example, reduced levels of SMN protein (30).…”
mentioning
confidence: 54%
“…Although patients within families exhibited identical alterations in the SMN gene, they showed variations in disease phenotype indicative of other disease modifying genes. Thus, it was concluded that Gemin2 mutations are rare and they do not function as a disease modifier in SMA (29). However, this study did not address the point whether levels of Gemin2 protein are altered in these patients by mechanisms such as, for example, reduced levels of SMN protein (30).…”
mentioning
confidence: 54%
“…However, homozygous deletions of NAIP may simply reflect larger chromosomal deletions involving both SMN1 and SMN2. Likewise, phenotypic variations between siblings with identical 5q13 haplotypes did not correlate with mutations or differences in expression of Gemin2 (SIP1) [68]. H4F5 (SERF1) is closer to SMN1 on chromosome 5 than any other known gene.…”
Section: Candidate Modifying Genes For Smamentioning
confidence: 90%
“…Low levels of SMN result in the SMA phenotype, but alterations in the splicing of Gemin2 mRNA may also be involved in the disease pathogenesis of SMA (Aerbajinai et al 2002;Helmken et al 2000). Recently, a potential C. elegans homologue of the Gemin2 gene has been predicted, (The C. elegans Sequencing Consortium 1998).…”
Section: Introductionmentioning
confidence: 97%